Effects of adding multiwall carbon nanotubes on performance of polyvinyl acetate and urea-formaldehyde adhesives in tropical timber species - Rodríguez-Zúñiga, Ana; Vega-Baudrit, José; Moya-Roque, Róger (Hindawi Publishing Corporation, 2015)
Multiwall carbon nanotubes (MWCNTs) functionalized with hydroxyl groups (MWCNTs-OH) have been incorporated into polyvinyl acetate (PVAc) and urea-formaldehyde (UF) adhesives utilized in tropical wood gluing. The Raman spectroscopy, the atomic force microscopy (AFM), and transmission electron microscopy (TEM) were used to describe the MWCNTs-OH. The adhesives were evaluated in three concentrations of MWCNTs-OH: 0% (control), 0.05%, and 0.1%. The evaluation included color, the distribution of MWCNTs-OH by TEM and AFM, thermal stability and viscosity of the adhesives, and shear strength (SS) of the glue line for nine tropical woods. AFM and TEM confirmed interaction of MWCNTs-OH with adhesives. The viscosity of the PVAc adhesive increases with added MWCNTs-OH. The incorporation of MWCNTs-OH in PVAc and UF resin produces wood adhesives with less brightness, less yellowness, and increased redness. The nanotubes in the adhesive improved the thermal stability of the composites and increased the entropy factor and energy of activation in the kinetic decomposition of the resin. In relation to SS, MWCNTs-OH in any of the two concentrations had no significant effect on SS in dry condition in half of the species studied glued with PVAc adhesive, whereas, for UF-adhesive, the SS and percentage of wood failure improved in most of the 9 species studied.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84940754701&partnerID=40&md5=1821f371fbf5ca780f855a8c5c875e01
Keywords: Adhesivos, carbón, microscopia electrónica, madera, viscosidad; Adeshivos; Carbón; Microscopia electrónica; Madera; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Forest engineering